1996
DOI: 10.1016/0020-7292(96)02685-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth patterns of the humeral and femur length in a multiethnic population

Abstract: There appear to be definite differences in growth of limb length between the different Malaysian ethnic groups and this should be taken into account when growth charts are used and when fetal weight formulas are calculated using limb lengths. The limitation of this study was that the numbers of subjects studied were small. Larger studies will be able to confirm or refute the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…In general, studies conducted in Asia or in populations of Asian immigrants in Europe have found that fetal anatomical parameters are smaller at given gestational ages than in Caucasian populations21–25. In addition, differences in femur and humerus length have been observed among Asian populations of different ethnicity26.…”
Section: Discussionmentioning
confidence: 99%
“…In general, studies conducted in Asia or in populations of Asian immigrants in Europe have found that fetal anatomical parameters are smaller at given gestational ages than in Caucasian populations21–25. In addition, differences in femur and humerus length have been observed among Asian populations of different ethnicity26.…”
Section: Discussionmentioning
confidence: 99%
“…Most currently available nomograms were derived from developed, primarily Caucasian, populations. Maternal race/ethnicity influence fetal growth2–4, as do maternal and environmental factors5. For example, maternal human immunodeficiency virus (HIV) and malaria infection, chronic undernutrition, and micronutrient deficiency are often endemic in low‐resource populations and are associated with lower birth weight6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that maternal ethnicity may influence long bone length, although Weisz et al found no evidence of ethnic differences. In this study, we did not consider maternal ethnicity, which may represent a limitation.…”
Section: Discussionmentioning
confidence: 99%